Impact of Branched Chain Amino Acid on Muscle Mass, Muscle Strength, Physical Performance, Combined Survival, and Maintenance of Liver Function Changes in Laboratory and Prognostic Markers on Sarcopenic Patients With Liver Cirrhosis (BCAAS Study): A Randomized Clinical Trial - Singh Tejavath, Arun; Mathur, Amit; Nathiya, Deepak; Singh, Pratima; Raj, Preeti; Suman, Supriya; Mundada, Payal Ramakant; Atif, Sheikh; Rai, Ramesh Roop; Tomar, Balvir Singh (Frontiers in Nutrition, 2021)
Background: This study aimed to investigate the long-term effects of branched-chain amino acids (BCAAs) supplementations on the parameters associated with improved prognosis in sarcopenic patients with liver cirrhosis (LC) and evaluate its impact on cirrhotic-related events. Methods: A 24-week, single-center, randomized, open-label, controlled, two cohort parallel-group intervention study was carried out by comparing the efficacy of BCAAs against lactoalbumin (L-ALB) on 106 sarcopenic patients with LC. The BCAA (intervention) group was treated with 7.2 g BCAA per dose, whereas the L-ALB group was treated with 6.3 g of L-ALB. The primary outcome was to assess the effect of BCAA on the parameters of sarcopenia, such as muscle mass, muscle strength, and physical performance. The secondary outcomes were to study the combined survival and maintenance of liver function changes in laboratory and prognostic markers over the duration of 6 months. Results: The treatment with BCAA leads to the significant improvement in sarcopenic parameters, such as muscle strength, muscle function, and muscle mass. The total cirrhotic-related complications and cumulative event-free survival occurred fewer in the BCAA group than in the L-ALB group. In addition, prognostic markers improved significantly in the study. Conclusion: The current study demonstrated that long-term BCAAs supplementation improved sarcopenia and prognostic markers in patients with advanced LC.